Autophagy in cardiac metabolic control: Novel mechanisms for cardiovascular disorders. (4th July 2016) - Yang, Yufei; Zhao, Cong; Yang, Pingzhen; Wang, Xianbao; Wang, Lizi; Chen, Aihua
Abstract: As an extensively studied quality control system, autophagy is responsible for clearance of dysfunctional organelles and damaged marcomolecules in cells. In addition to its biological recycling function, autophagy plays a significant role in the pathogenesis of metabolic syndromes such as obesity and diabetes. In particular, metabolic disorders contribute to cardiovascular disease development. As energy required to maintain cardiac cells functional is immense, disturbances in the balance between anabolic and catabolic metabolism possibly contribute to cardiovascular disorders. Therefore, an urgent need to expand our knowledge on the role of autophagy on the metabolic regulation of hearts emerges. In this review, the potential relationship between autophagic activity and cardiac metabolism is explored and we also discuss how dysregulated autophagy leads to severe cardiac disorders from the perspective of metabolic control.